The deepening divide : inequality in the information society - Dijk, Jan A. G. M. van (Sage, 2005)
The Deepening Divide: Inequality in the Information Society explains why the digital divide is still widening and, in advanced high-tech societies, deepening. Taken from an international perspective, the book offers full coverage of the literature and research and a theoretical framework from which to analyze and approach the issue. Where most books on the digital divide only describe and analyze the issue, Jan van Dijk presents 26 policy perspectives and instruments designed to close the divide itself.